An impact origin for hydrated silicates on Mars: A synthesis. Issue 5 (21st May 2013) - Tornabene, Livio L.; Osinski, Gordon R.; McEwen, Alfred S.; Wray, James J.; Craig, Michael A.; Sapers, Haley M.; Christensen, Philip R.
Abstract : [1] Recent Mars‐orbiting spectrometers continue to detect surface materials containing hydrated silicates, particularly clays and amorphous phases (e.g., silica glasses), concentrated within the heavily cratered Noachian highlands crust. This paper provides a review, summary, and synthesis of observations from terrestrial impact structures with current Martian data. It is suggested that numerous and frequent impacts into the volatile‐rich silicate crust of Mars, through direct and indirect impact‐generated mechanisms, represent a plausible hypothesis that can explain the widespread distribution of hydrated silicates in the surface and subsurface of the heavily cratered Noachian highlands crust largely independent of climate. In addition to impact‐generated hydrothermal activity, devitrification, autometamorphism, and the voluminous production of impact "damaged" materials that are susceptible to alteration must be considered. When taken together, a drastically different early climate on Mars, in which water is stable at the surface for extended periods of time, cannot be ruled out; however, it is noted here that these additional impact mechanisms can operate and thereby extend the range of possible alteration settings to include climate conditions that may have been predominately colder and drier. Such a climate would not be dissimilar to the conditions of today, with the important exceptions of a higher geothermal gradient, and punctuated thermal disturbance to the cryosphere and hydrosphere from igneous activity and an exponentially higher impact flux. Key Points: Frequent impacts into the volatile‐rich crust can produce hydrated silicates. Does not require drastic climate change. Additional impact‐induced alteration mechanisms explained.